2014
DOI: 10.1002/2014gl060018
|View full text |Cite
|
Sign up to set email alerts
|

Winter fog is decreasing in the fruit growing region of the Central Valley of California

Abstract: The Central Valley of California is home to a variety of fruit and nut trees. These trees account for 95% of the U.S. production, but they need a sufficient amount of winter chill to achieve rest and quiescence for the next season's buds and flowers. In prior work, we reported that the accumulation of winter chill is declining in the Central Valley. We hypothesize that a reduction in winter fog is cooccurring and is contributing to the reduction in winter chill. We examined a 33 year record of satellite remote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…In a more recent study, Williams et al (2015) found that ongoing urbanization, specificly the influence of the UHI is responsible for the decrease of fog in southern California. A satellite data analysis showed that the fog frequency also decreased strongly in the California Central Valley (Baldocchi and Waller, 2014). The potential contributions of climate change, increase of air quality and agricultural practices are mentioned, however not analyzed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study, Williams et al (2015) found that ongoing urbanization, specificly the influence of the UHI is responsible for the decrease of fog in southern California. A satellite data analysis showed that the fog frequency also decreased strongly in the California Central Valley (Baldocchi and Waller, 2014). The potential contributions of climate change, increase of air quality and agricultural practices are mentioned, however not analyzed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Aridification in the western United States has already been linked to large-scale tree dieoffs and other vegetation changes (20)(21)(22)(23). In California, where overall aridity has increased in recent decades (18) and coastal and inland fog have declined dramatically (24,25), aridification is predicted to dominate the effects of climate change on natural vegetation over the coming century (18,19,26). Although directional declines in species richness in western US grasslands in response to long-term drying trends are not yet documented, they may be expected based on evidence that grassland species richness is higher in wetter than drier years, geographical locations, and experimental treatments (27)(28)(29).…”
mentioning
confidence: 99%
“…Areas of complex topography are characterized by unique meteorological conditions that influence Q si : reoccurring cloud patterns such as afternoon thunderstorms [ Olyphant , ] and mountain wave clouds [ Grubišić and Billings , ], topographically driven gradients in water vapor [ Feld et al ., ], stable inversions causing persistent fog [ Underwood et al ., ; Lundquist and Cayan , ; Baldocchi and Waller , ] and trapping aerosols [ De Young et al ., ; McMeeking et al ., ], and reduced optical depths from water vapor, aerosols, and air mass due to higher elevations [ Marty et al ., ; Yang et al ., ].…”
Section: Methodsmentioning
confidence: 99%